Coordination Dynamics of Upper Limbs in Swimming: Effects of Speed and Fluid Flow Manipulation. Issue 3 (2nd July 2020) - Guignard, Brice; Rouard, Annie; Chollet, Didier; Bonifazi, Marco; Dalla Vedova, Dario; Hart, John; Seifert, Ludovic
ABSTRACT: Purpose : Motor outputs are governed by dynamics organized around stable states and spontaneous transitions: we seek to investigate the swimmers' motor behavior flexibility as a function of speed and aquatic environment manipulations. Method : Eight elite male swimmers partook an eight-level incremental test (4% increment from 76% to 104% of their mean speed on 200 m front crawl) in a quasi-static aquatic environment (pool). Swimmers then partook another incremental test at similar effort in a dynamic aquatic environment (swimming flume) up to maximal speed. Stroke rate (SR), index of coordination (IdC) and intersegmental coupling of the upper limbs were computed from the inertial sensors located on the upper limbs and the sacrum. Results : With speed increase, SR values presented a steeper linear increase in the pool than in the flume. IdC values increased also in the pool but remained stable in the flume. Individual SR and IdC vs. speed increase displayed second-order polynomial dynamics, indicative of adaptive flexibility with a range of extremum values more restricted in the flume. Finally, a reduction of the in-phase coordination pattern was noted with flume speed increase. Conclusions : Action possibilities were strongly constrained in the flume at the highest speeds as the fluid flow led to discontinuity in the propulsive actions of the upper limbs and lack of in-phase inter-segmental coordination. This highlights that the behavioral flexibility was restricted in the flume in comparison to the pool, in which the exploitation of opportunities for action involved a larger number of degrees of freedom in the movement.